Political pluralism as a factor in the development of modern society and state - Andreev, Sergey D.; Bitsieva, Emma V.; Lepeshkina, Olga V.; Polonsky, Dmitry M.; Savchenko, Marina S. (Linguistics and Culture Review, 2021)
This paper presents the results of a study devoted to the legal phenomenon of political pluralism as a factor in the development of modern society and the state by the example of classical democratic countries. At the same time, attention is focused on such components of political pluralism as formalization of freedom of speech and assembly; a multi-party system, as well as a mechanism for coordinating the interests of various social groups at the parliamentary level. It was found that the most acceptable is the model operating in the FRG, since it allows people to find a balance between guarantees of political diversity, such as freedom of speech and the right to public events. The interaction between civil society institutions and parliamentarians is especially advisable when making decisions in the domestic and foreign policy of the state.